Trainer Kit for Velocimetry Thermodynamics Lab Dice Throwing - Muhammad Prihadi Eko Wahyudi; Natalia Parhusip; Fauzun Atabiq; Qoriatul Fitriyah (JURNAL INTEGRASI, 2023)
The Trainer Kit is one of the tools that supports the learning process of the Thermodynamics Lab Course. The objects ejection tool design is created with a 3D printed catapult movement system. The main components of the objects Ejection Speed ​​Trainer Kit are: Use the ultrasonic sensor HC-SR04 as a guide for the desired firing distance, a stopwatch as a measure of time spent throwing objects using the TTP223's capacitive touch as a start and stop clock. Load cell as a measure of the weight of the objects. Meter reading results are displayed on a 20x4 LCD with an i2c module and calculation of velocity values ​​using Visual Basic 6.0. Results of a load cell experiment measuring 6 different materials weighing between 5 and 63 g with an average measurement error of 1.2%. As result of ultrasonic examination measured in increments of 3 to 100 cm, the measurement error is 0% at the maximum distance of 70 cm, and the error is 1.1% at 70 cm or more. The result of the timer experiment using TTP223 in 15 tests has an arithmetic error of 0.37%.